Contact Dermatitis in Tertiary Hospital: A 2-year Retrospective Study - Efenina Ginting; Damayanti Damayanti; Deasy Fetarayani; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Contact dermatitis (CD) is a skin inflammatory caused by allergen or irritant that generates public health impact. CD is classified into two types, based on its etiological perspective, namely allergic contact dermatitis (ACD) due to a hypersensitivity type IV reaction and irritant contact dermatitis (ICD), which is a non-immunological reaction. Purpose: To determine the profile of CD patients at Dermatology and Venereology Outpatients Unit of Dr. Soetomo General Academic Hospital Surabaya in January 2018 – December 2019. Methods: A retrospective study by observation and recording data. The results of the data recap were then processed using Microsoft Excel to obtain conclusions. Result: The results obtained were ACD (61.9%) and ICD (38.1%), aged 26-45 years (32.7%), female (79.3%). The most frequent occupation was housewives (25.3%), followed by private employees (24.5%). The most suspected causative substance was cosmetic (47.7%). The most common skin disease history was food allergy (11%), followed by drug allergy (2.8%), and atopic dermatitis (2.3%). The most frequent manifestation was acute (69.8%), with the most clinical presentation was erythematous macules (35%). Most therapies were given in combination (73.6%), with antihistamines (61%) and topical corticosteroids (49.2%) were the most prescription drug. Conclusion: ACD was more common than ICD, mostly in a female, dominated in the 26-45 years old. Housewife was the most occupational. Cosmetic was the most suspected causative substance. Food allergy was the most skin disease history. Acute was the most frequent manifestation. Erythematous macules were the most clinical presentation. Antihistamine and corticosteroid are the most common drug in combination therapy.